Tourists’ Recommendations: Socio-demographic Analysis (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
In tourism, information can be treated as the most important factor influencing consumer behaviour. Word-of-mouth is one of the possible ways to transfer information. It is a form of communication – through recommendations - which involves consumers discussing their experience after service consumption. The aim of this paper is to highlight the differences in the frequency of spreading information through word-of-mouth among consumers – tourists of different socio-demographic characteristics (gender, age and, education). The survey was conducted in the period from October to December 2018 on a sample that included 228 respondents from the territory of AP Vojvodina. Based on a literature review and research objective, three hypotheses have been set. The cross-tabulation method was used for testing the proposed hypotheses.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.